Natural Killer Cell Recognition and Control of Epithelial Cancers. Issue 4 (July 2022) - de Souza Fernandez Pereira, Marcelo; Carr, David R.; Gatti-Mays, Margaret E.; Olsen, Mallery R.; Setty, Bhuvana A.; Shahwan, Kathryn T.; Lee, Dean A.
Abstract: Natural killer (NK) cells possess an innate ability to recognize cancer and are key mediators of cytotoxic efficacy for anticancer antibodies. Recent advances in the ability to generate, qualify, and safely infuse NK cells have led to a wide variety of clinical trials in oncology. Although their efficacy is best established for liquid cancers, their potential application in solid cancers has received increased attention. Here, we provide general background across a disparate group of exemplary solid tumors for which there is evidence for an NK cell role, discuss NK cell recognition motifs specific to each and murine and human studies of each that are supportive of NK cell adoptive immunotherapy, and end with special considerations relevant to the solid tumor microenvironment.